2009
DOI: 10.2320/matertrans.m2009186
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tensile Strength and Plasticity of Zr-Cu-Al Bulk Glassy Alloys at Cryogenic Temperatures

Abstract: No data are available about mechanical behavior of bulk glassy alloys (BGAs) in tension at cryogenic temperatures. In this study, we investigated the effect of temperature on the mechanical behavior of ternary eutectic and hypoeutectic Zr-Cu-Al BGAs fabricated by an arc tilt casting method. Tensile tests were performed for the BGA plates with gauge dimensions of 5 mm in length, 1.2 mm in width and 0.5 mm in thickness at temperatures of 295, 223, 173 and 77 K, at an initial strain rate of 5 Â 10 À4 s À1 . Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
4
20
1
Order By: Relevance
“…Fig. 1a shows the tensile failure strength r f of Vitreloy 1 as a function of the environmental temperature T. The failure strength increases gradually with decreasing temperature from 300 to 77 K, which is consistent with the observations in other Zr-based metallic glasses [32][33][34][35]. However, with further decreasing temperature to 20 K, the failure strength is found not to increase any more, but starts to decrease instead.…”
Section: Methodssupporting
confidence: 78%
“…Fig. 1a shows the tensile failure strength r f of Vitreloy 1 as a function of the environmental temperature T. The failure strength increases gradually with decreasing temperature from 300 to 77 K, which is consistent with the observations in other Zr-based metallic glasses [32][33][34][35]. However, with further decreasing temperature to 20 K, the failure strength is found not to increase any more, but starts to decrease instead.…”
Section: Methodssupporting
confidence: 78%
“…In contrast, some recent results have indicated that the tensile plastic deformation of BMGs occurs at cryogenic temperature on the basis of experiments performed using Zr CuAl BMG, 7) ZrCu based BMG 8) and ZrNiCuAl BMG. 9) These results suggest that the tensile plastic deformation behavior of BMGs depends on the strain rate and temperature.…”
Section: Introductionmentioning
confidence: 89%
“…On the other hand, the strengthened materials at low temperature usually behave more brittle. However, very interestingly, it is reported that BMGs at cryogenic temperature show enhanced plasticity in compression [1][2][3][4][5][6][7][8], even in tension [9,10]. Such plasticity improvement was attributed to multiple-nucleation of shear bands at low temperature [1,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to crystalline alloys, BMGs usually exhibit higher strength with the decrease of the ambient temperature [1][2][3][4][5][6][7][8][9][10]. Its underlying mechanism has been discussed in terms of shear transformation zones (STZs) [1,3,5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%